Accelerating collaboration to find a cure: a nonprofit's evolving business model. Issue 1 (5th January 2015) - Dumas, Colette; Foley, Susan; Hunt, Pat; Weismann, Miriam; Williamson, Aimee
Abstract : Synopsis: This is a field‐researched case about a nonprofit organization, the Accelerated Cure Project (ACP), dedicated to accelerating advances toward a cure for multiple sclerosis (MS). Inspired by the successful open source software development platform, ACP brings the strengths of that platform into the medical research and development environment. At the opening of the case, Robert McBurney, an Australian scientist with extensive experience in the biotech world, has been named CEO. McBurney and his team want to use ACP's bio‐sample and data Repository to drive innovation in the search for the cure for MS by fostering collaborative research and development across research institutions, pharmaceutical and bio‐tech companies. To encourage such collaboration ACP waives its rights to potentially lucrative Intellectual Property. This decision to foster collaboration at the expense of revenue sources appears problematic, since ACP does not have the staff or resources to undertake fundraising at the scale needed to fund current projects. ACP chooses to serve instead as an open access research accelerator making an impact on the field by functioning as an innovation driver rather than a profit maker. Is this an innovative recipe for success in finding a cure for MS or a recipe for financial disaster for ACP? Research methodology: Interviews provided the primary source of data for this case. Four semi‐structured interviews were conducted with the CEO of ACP, the Vice President of Scientific Operations, and a member of the organization's Board of Trustees, a collaborating university researcher, and the President of a bio‐tech company working with ACP. Interview data was supplemented with additional information from ACP's web site, news reports, McBurney's comments at Suffolk University's Global Leadership in Innovation and Collaboration Award event, and follow‐up conversations. Relevant courses and levels: This case is intended for use in an undergraduate course examining strategic management issues midway through the term. The case discussion can center on issues relating to: first, the development of the business model; second, revenue resources and fundraising. Students are expected to spend two to three hours of outside preparation reviewing concepts of change leadership and the collaborative enterprise business model. They should read the case materials and brainstorm options for improved change leadership. The case can be taught in one two‐hour class period. Theoretical basis: The purpose of this case is to introduce students to the strategic management and funding challenges faced by an organization that is using a non‐traditional business model in an increasingly complex environment. As a result of discussing this case, students should be able to: first, examine strategic organizational strengths, analyze opportunities created by business, market and environmental factors, and strategize to minimize weaknesses and to address threats identify an organization's strategic focus; recognize and recommend options at crucial decision making junctures in a business situation; second, assess an organization's revenue model; analyze how this model can be improved; third, analyze the functionality and sustainability of an organization's business model.